Monotropein: A comprehensive review of biosynthesis, physicochemical properties, pharmacokinetics, and pharmacology - Wu, Mingquan; Lai, Huabing; Peng, Wei; Zhou, Xu; Zhu, Liyang; Tu, He; Yuan, Kezhu; Yang, Zhirui (Frontiers in Pharmacology, 2023)
Monotropein, a principal natural compound in iridoid glycosides extracted from Morindae officinalis radix, has potent pharmacological activities. To understand and utilize monotropein, we systematically summarized the studies on monotropein, including its biosynthetic pathway, physicochemical properties, pharmacokinetics, and pharmacology. Interestingly, we found that the multiple bioactivities of monotropein, such as anti-osteoporosis, anti-inflammation, anti-oxidation, anti-nociception, and hepatic or renal protection, are closely associated with its capability of downregulating the nuclear factor-κB signaling pathway, inhibiting the mitogen-activated protein kinase signaling pathway, attenuating the activation of nuclear factor E2-related factor 2/heme oxygenase-1 signaling pathway, and regulating the mammalian target of rapamycin/autophagy signaling pathway. However, the clinically therapeutic effects and the potential problems need to be addressed. This review highlights the current research progress on monotropein, which provides a reference for further investigation of monotropein.